PENGARUH KEBIJAKAN DIVIDEN DALAM MEMODERASI FINANCIAL PERFORMANCE TERHADAP RETURN SAHAM PADA SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B2041171022, YOPINUS BOBI (Universitas Tanjungpura, 2020)
This study aimed to examine the effect of dividend policy proxy by Dividend Payout Ratio as a moderation of financial performance proxy by Debt to Equty Ratio, Free Cash Flow and Price to Book Value as well as inflation as a control variable for stock returns. The research method used was quantitative study using SPSS 20 assistance, the population in this study were agricultural companies listed on the Indonesia Stock Exchange during the period between 2013 and 2017. Samples were selected by purposive sampling technique with the criteria of continually having financial statements from 2013 to 2017. The results show that inflation and Debt to Equty Ratio have a negative influence on stock returns. Whereas Free Cash Flow and Price to Book Value have a positive influence on stock returns. Other results show that dividend policy does not moderate inflation and Debt to Equty Ratio to stock returns. In this case dividend policy applies as a potential moderation variable. Whereas Free Cash Flow and Price to Book Value have an influence on stock returns through dividend policy, in this case the policy dividend applies as a pure moderation variables. Recommendations for this study are expected to further add other variables that are thought to influence stock returns to be the object of research both internal and external factors. Examining returns in other business sectors that are still rarely studied. Increase the time period of the study because it will better know how the effect occur if the study is conducted in a longer period. Keywords : Financial Performance, Stock Return, Dividend PolicyDAFTAR PUSTAKAAndiantyo, Prakosa., Sihombing, Pardomuan, dan Kusumastuti Yani, S. (2018). Pergerakan Indeks Harga Saham Sektor Pertanian Di Bursa Efek Indonesia. Buku 2 : “Hukum, Politik, Manajemen, Ekonomi, Akuntansi, Konseling, Desain dan Seni Rupa. ISSN (P) : 2460 – 8696. ISSN (E) : 2540 – 7589.Agus, Sartono.(2014).Manajemen Keuangan:Teori dan Aplikasi. Edisi Keempat. Yogyakarta:BPFE Arikunto, S. (2013). Prosedur Penelitian. Jakarta: Rineka Citra Anwar Sanusi. (2011). Metode Peneltian Bisnis. Jakarta: Salemba Empat. Bambang, Riyanto. (2001). Dasar-Dasar Pembelanjaan Perusahaan. Edisi Keempat, Cetakan Ketujuh. BPFE. Yogyakarta Brigham, Eugene.F dan Joel F. Houston. (2006). Fundamental Of Financial Mangement, Dasar-dasar Manajemen Keuangan, Buku satu, Edisi Sepuluh, Alih bahasa Oleh Ali Akbar Yulianto . Jakarta: Salemba Empat. . (2014). Dasar-dasar Manajemen Keuangan. Penerjemah Ali Akbar Yulianto. Jakarta: Salemba Empat. Brigham, Eugene F., dan Daves, Philip R., 2004, Intermediate Financial Management, Eight Edition, Thomson, South-Western, Mason, Ohio, USA. Bungin, B. (2013). Metodologi Penelitian Sosial & Ekonomi (format-format Kuantitatif dan Kualitatif Untuk Studi Sosiologi, Kebijakan Publik, Komunikasi, Manajemen, dan Pemasaran. Jakarta: Kencana Prenada Media Group. Darmadji, Tjiptono dan Hendy M. Fakhruddin. (2006). Pasar Modal di Indonesia. Salemba Empat. Jakarta. Fahmi, Irham. (2012). Pengantar Pasar Modal. Edisi 1. Alfabeta. Bandung. Ghozali, I. (2006). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro. . (2009). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro. Husnan, S. (2001). Dasar-dasar Teori Portofolio dan Analisis Sekuritas, Edisi Keempat, UPP AMP YKPN Yogyakarta. Indrawati, Ph.D. (2015). Metode Penelitian Manajemen dan Bisnis. Bandung: PT. Refika Aditama. Jogiyanto. (2009). Teori Portofolio dan Analisis Investasi, Edisi Keempat cetakan ke 1. Yogyakarta: BPFE. Kasmir. (2010). Pengantar Manajemen Keuangan. Jakarta: Kencana . (2011). Analisa Laporan Keuangan. PT Raja Grafindo Persada. Jakarta. . (2012). Analisa Laporan Keuangan. PT Raja Grafindo Persada. Jakarta. Kurniadi, Arif., Achsani Noer, A., & Sasongko, Hendro. (2013) Kinerja Keuangan Berbasis Penciptaan Nilai, Faktor Makroekonomi dan Pengaruhnya Terhadap Return Saham Sektor Pertanian. Jurnal Akuntansi dan Keuangan. 15 (2): 63-74. M. Iqbal. (2012). Pokok-pokok Materi Statistik (Stastistik Deskriptif). Jakarta: Bumi Askara Munawir, S. (2014). Analisis Laporan Keuangan. Yogyakarta: liberty Peni R. Pramono. 2008. Menilai Kinerja Manajer Lewat Laporan Keuangan. Jakarta: PT. Gramedia Riduwan. (2015). Belajar Mudah Penelitian Untuk Guru-Karyawan dan Peneliti Semula. Bandung: Alfabeta Riyanto, Bambang. (2001). Dasar-dasar Pembelajaran Perusahaan. Edisi Keempat, Cetakan ketujuh: BPFE Yogyakarta Sapto, Rahardjo (2006). Kiat Membangun Aset Kekayaan. Elex Media Komputindo, Jakarta. Samsul, Mohammad. (2006). Pasar Modal dan Manajemen portofolio. Erlangga: Jakarta. Sarwono, J. (2011). Path Analisis. Jakarta: PT Alek Media Komputindo Sawir, A. (2009). Analisa Kinerja Keuangan dan Perencanaan Keuangan Perusahaan. Jakarta: PT. Gramedia Pustaka Utama. Sugiyono. (2012). Statistik Untuk Penelitian. Bandung: Alfabeta ________. (2014). Metode Penelitian Kuantitatif Kualitatif dan R & D. Bandung: Alfabeta. ________.(2015). Metode Penelitian Tindakan Komprehenssif. Bandung: Alfabeta Suharyoko. (2012). Analsiis Pengaruh Debt Equty Ratio (DER) dan Earning Per Share (EPS) terhdap harga saham ektor perbankan yang terdapat di BEI. Tesis Universitas Tanjungpura Pontianak: Tidak diterbitkan Suharyadi dan Purwanto, S.K (2008). Statistika untuk Ekonomi dan Keungan Modern. Jakarta: Salemba Empat. Aggarwal., Bhasin., Sharma., Chhabra., Rajoura. (2005). A New Instrument (Scale) for Measuring the Socioeconomic Status of a Family : Preliminary Study. Indian Journal of Community Medicine, 30(4), 111-114. Supadi Dwi Budi Prasetyo & Amin M. Nuryatno. (2012) Pengaruh Faktor Fundamental Dan Risiko Sistematis Terhadap Return Saham Syariah. Media Riset Akuntansi, Auditing & Informasi. 12 (1). Supriyadi,Yoyon & Senjaya, Edih. (2013) Pengaruh Kinerja Keuangan Terhadap Harga Saham. Jurnal Ilmiah Ranggagading. 13(1): 31-44. Suryabrata, S. (2008). Metodologi Penelitian. Jakarta: Raja Grafindi Persada Tandelilin, Eduardus. (2001). Analisis Investasi dan Manajemen Risiko. Edisi Pertama, Yogyakarta: BPFE. Sutrisno. (2012). Manajemen Keuangan Teori, Konsep, dan Aplikasi. Ekonisia, Kampus Fakultas Ekonomi UII. Jakarta. Subramanyam, K.R. dan John J. Wild. (2010). Analisis Laporan Keuangan (Financial Statement Analysis). Edisi Kesepuluh. Terjemhan Dewi Yanti. Jilid 2. Jakarta: Salemba Empat.